PEMBERDAYAAN UKM INDUSTRI MANUFAKTUR DI RANDU, KECAMATAN KENJERAN KOTA SURABAYA - Sasongko, Sukendro Broto; Suparjo, Suparjo; Suparto, Suparto (Jurnal Abdi Insani, 2024)
Recently, the industrial of manufacturing has grown into industry 4.0 and its progress significantly enhanced. The activity of public-serving is to develop the ability of small companies to manufacture. Regarding it, a semi-auto welding machine is required to revolute their performance in the small industry. Further, the welding knowledge obtained by training. That is, the public serving is at CV. Manshurin.  The methods of public-serving aim to develop the small company. The first activity of it has done by upgrading the welding machine. Thus, training for employees to the welding characteristics is important. An invited trainer in a short class meeting is to deliver the information on the welding morphology and guide to operate the semi-automatic welding machine. Regarding it, the employee training has been done offline. the employee’s knowledge of the welding system increased. Further, the employee of CV. Manshurin skills are also increased. Therefore, they can operate a new welding machine (a semi-automatic welding machine). That is, those facts concluded that the employees receive the enhancement of knowledge, especially the morphology of the welding characteristic. In which, its formations are presented by a trainer who is invited to its training day. Thus, a semi-automatic welding machine improves the quality of the welding result.